Applicability of the probiotic Lactiplantibacillus plantarum BFL as an adjunct culture in a dry fermented sausage - Sirini, Noelí Estefanía (2023)
The addition of probiotic bacteria to a meat batter allows the development of functional fermented sausages. The aim of this work was to study the effect of microencapsulated Lactiplantibacillus plantarum BFL (EP) and as free cells (FP) on microbiological, physicochemical, and sensory parameters of fermented sausages during the drying stage and on the product ready for consumption. The microencapsulation of L. plantarum BFL did not improve its viability during the drying stage. In addition, sausages inoculated with L. plantarum BFL (FP and EP) caused lower residual nitrites values, pH values and Escherichia coli counts than the Control (C). However, only the presence of free cells of L. plantarum BFL (FP) caused a decrease in the Enterobacteriaceae and mannitol salt-positive Staphylococcus counts. In the sensory analysis, no significant differences were found in the acceptability of the different sausages. However, the acidity in probiotic sausages (FP and EP) was an attribute that consumers highlighted. The probiotic L. plantarum BFL could adapt and survive at high doses in the matrix of an industrial fermented sausage. Therefore, its use could represent a strategy both for biocontrol of pathogens and for the development of functional meat products.